KONTEKSTUALISASI PEMBELAJARAN PAI BERBASIS KEHIDUPAN - Fathor Rahman (Fakultas Tarbiyah, Universitas Ibrahimy, 2020)
Islamic education learning to date has not shown significant results. Islamic education learning tends to be theoretical and unrealistic with life. The implementation of religion is more symbolic ritual. Islamic religious education should be able to create individuals capable of applying Islamic values in every aspect of life. This classic problem is urgent to find a solution, because Islam is a source of values, ethics and outlook on life of every Muslim community. Islamic education contextualization efforts are absolutely necessary in educational institutions. So reorienting the learning approach that oversees and gives birth to output that can contribute to the environment becomes important to do in the world of education. This paper presents a solution to the existence of life-based Islamic education learning. Life-based learning is a learning approach that forms a contextual-integrative-holistic learning environment. One of the efforts made in implementing this approach in Islamic education learning is that in addition to the curriculum it must be designed based on the needs of students who have unique, characteristics, and potentials as well as different developments and dynamics.Islamic education curriculum is also designed with the perspective of local and global excellence, while the teacher is the curriculum executor who will oversee and print students according to educational goals. In this case the teacher requires standards of academic qualifications and competence.